Role of AMPK/mTOR-independent autophagy in clear cell renal cell carcinoma. (21st October 2020) - Radovanovic, Milan; Vidicevic, Sasenka; Tasic, Jelena; Tomonjic, Nina; Stanojevic, Zeljka; Nikic, Predrag; Vuksanovic, Aleksandar; Dzamic, Zoran; Bumbasirevic, Uros; Isakovic, Aleksandra; Trajkovic, Vladimir
Abstract : We examined the status and role of autophagy, a process of lysosomal recycling of cellular material, in clear cell renal cell carcinoma (ccRCC). Paired samples of tumor and adjacent non-malignant tissue were collected from 20 patients with ccRCC after radical nephrectomy. The mRNA levels of apoptosis ( BAD, BAX, BCL2, BCLXL, BIM ) and autophagy ( ATG4, BECN1, GABARAP, p62, UVRAG ) regulators were measured by RT-qPCR. The protein levels of autophagosome-associated LC3-II, autophagy receptor p62, apoptotic marker PARP, as well as phosphorylation of autophagy initiator Unc 51-like kinase 1 (ULK1), its activator AMP-activated protein kinase (AMPK) and 4EBP1, the substrate of ULK1 inhibitor mechanistic target of rapamycin (mTOR), were analyzed by immunoblotting. The mRNA levels of pro-apoptotic BAX, anti-apoptotic BCLXL and pro-autophagic ATG4, p62 and UVRAG were higher in ccRCC tumors. Autophagy induction was confirmed by an increase in phospho-ULK1 and degradation of the autophagic target p62, while apoptotic PARP cleavage was unaltered. AMPK phosphorylation was reduced and 4EBP1 phosphorylation was increased in ccRCC tissue. The expression of apoptosis regulators did not correlate with clinicopathological features of ccRCC. Conversely, high mRNA levels of ATG4, GABARAP and p62 were associated with lower tumor stage, as well as with smaller tumor size and better disease-specific 5-year survival ( ATG4 and p62 ). Accordingly, low p62 protein levels, corresponding to increased autophagic flux, were associated with lower tumor stage, reduced metastasis and improved 5-year survival. These data demonstrate that transcriptional induction of autophagy in ccRCC is accompanied by AMPK/mTOR-independent increase in ULK1 activation and autophagic flux, which might slow tumor progression and metastasis independently of apoptosis.